Social and Educational Functions of [Literary] Narratives - Štubňa, Pavol (Poznańskie Studia Slawistyczne, 2020)
The study deals with social and educational functions of (literary) narratives – both oral and written – in everyday life of a socially grounded individual. Narratives (or stories told or read) play an essential role in building and strengthening social bonds within a community (by spending time together, informing its members of preferred social values and behaviour patterns, etc.) The author sustains that narratives circulating within a particular community (or ethnic group, nation) should be viewed and analyzed from the perspective of cultural anthropology. As an educational tool, stories are utilized not only in families and schools, but also in penitentiary and correctional institutions or in public reading courses. The author also pays attention to particular structural components of “captivating” narratives (such as novelty, surprise, cognitive and/or emotional relevance to the reader, etc.) and so-called narrative universals – themes, types of characters, plots and settings that are common to all cultures worldwide (such as romantic love, human desires and needs, sacrifice, etc.).